Three times higher hatching rates of brown-marbled grouper, epinephelus fuscoguttatus under Green light than white light - Mukai, Yukinori (2014)
Egg hatching rates vary under different environmental conditions such as temperature, salinity, and light conditions. Light conditions are important for aquatic living things, as they affect growth and development. A few studies have been done on teleost eggs regarding optimum light conditions for incubation. For example, haddock eggs show that they are not affected by light intensity. Walleye pollock requires dark condition for the egg incubation, high light intensity, while rainbow trout eggs incubation is optimum under dim light conditions. These studies show that light conditions for egg incubations are species-specific related to the characteristics of spawning grounds. Brown-marbled grouper, Epinephelus fuscoguttatus is an important species for aquaculture in Southeast Asia. However, there are only a few studies about its early developmental stage. Still we do not know what light condition is optimum for egg incubation of brown-marbled grouper. Therefore, this study was conducted to examine optimum light wavelength and intensity for the incubation of brown-marbled grouper eggs. Light emission diode (LED) lamps were used to examine egg hatching rates. Brown-marbled grouper eggs were obtained from the brood stock of the IIUM hatchery. The eggs were incubated in 40 L triplicate aquaria in dark room, using different light wavelengths of LEDs; white as a control, blue, green, yellow and red with light intensities 0.53, 2.7 and 13.3 µmoles/m²/s respectively. Results of two-way ANOVA showed that light intensities had no significant difference, while light wavelengths had significant difference (p<0.05). Results of Tukey’s post hoc test showed that green light wavelength was significantly higher than white and yellow light wavelengths (p<0.05). Green light (2.7 µmoles/m²/s) showed almost three times higher than white light (2.7 µmoles/m²/s).